PENGENALAN ARSITEKTUR RUMAH TRADISIONAL DESA BELEK SEMBALUN LAWANG LOMBOK DENGAN MENGGUNKAN ANIMASI 3D MENGGUNAKAN BLENDER SEBAGAI MEDIA PEMBELAJARAN - Hariman Bahtiar; Muhammad Djamaluddin (Fakultas Teknik Universitas Hamzanwadi, 2020)
Utilizing multimedia to convey information is one way to publicize the traditional architecture of the Lombok area especially the traditional house of Belek Sembalun Lawang Village in the form of 3D animation using a blender software that can be used as a learning medium. Belek Village is a large village/village holding village that was first made consisting of seven houses which were the forerunner of Sembalun Village. By using this 3D animation it is expected to provide solutions and alternatives in the process of introduction and learning about traditional architecture of the Lombok traditional house, especially the Belek village traditional house so that the learning process and the identification become more unique and interesting, as well as learning and introduction media for the traditional village of Belek , this 3D animation can also benefit in the effort to publicize and document the history and culture of Sembalun Lawang Village.DOI : 10.29408/jit.v3i1.1808